The scale of assessment of methodologically heterogeneous articles for integrative reviews - Valencia Contrera, Miguel (Revista Cuidarte, 2022)
The Scale of Assessment of Methodologically Heterogeneous Articles for Integrative Reviews (EAMH, for its acronym in Spanish)1 was recently published. This scale was developed in response to the growing need to ensure the quality of results in integrative reviews. The proposal provides guidelines on basic criteria that any article must meet to be included in the analysis of the results.The scale has six yes/no evaluation questions. Each “YES” answer scores one point; therefore, the scale score ranges from zero to six points and is interpreted as follows: From 0 to 3 points “article not recommended for analysis”; from 4 to 5 points “article suitable for analysis,” and, finally, 6 points “article ideal for analysis.” The results of applying this scale to analyze articles published in Cuidarte journal between 2021 and April 2022 will be presented below (see Table 1). The database was stored in Mendeley Data2.After analysis, 13.4% (n=30) of the articles used as a sample in the reviews analyzed3-11 scored from 0 to 3 points; this classification corresponds to “articles not recommended for analysis” since they failed to meet most of the elements evaluated by the questions contained in the scale. It should be noted that none of the articles used as a sample applied quality criteria in their respective samples; rather, level-of-evidence classifications, clinical questions, or Critical Appraisal Skills Programme (CASPe) checklists were used.The results indicate that applying the scale for assessing articles could improve the quality of the sample in integrative reviews. This scale is considered by its author as a proposal that contributes to achieving the full rigor that researchers should apply when scrutinizing articles. This document does not intend to criticize or question other colleagues’ works, especially when they have passed a review stage, but rather to contribute to the thoroughness that the process deserves, highlighting the importance of analyzing the quality of the articles selected in a review.How to cite this article: Valencia-Contrera Miguel Andrez. Escala de evaluación de artículos con metodologías heterogéneas para revisiones integrativas. Revista Cuidarte. 2022;13(2): e2744. http://dx.doi.org/10.15649/cuidarte.2744
Keywords: Integrative Review